INTERNET FINANCIAL REPORTING: THE CASE OF TURKEY - (:unkn) unknown (EUROMED PRESS, 2009)
Purpose - The purpose of our paper is to investigate the current state of internet financial reporting in light of the recent regulatory changes in the financial reporting environment of Turkish firms. Although these regulations only cover publicly listed firms, there has also been some usage of the internet as a means of disseminating financial information by large unlisted firms. However, we do not know the scale and scope of such voluntary financial disclosures or how they have changed over time. Design/methodology/approach - We survey the top 500 Turkish industrial firms on the 'Istanbul Chamber of Industry 500 list' (ICI500) to ascertain whether the recent regulatory changes have led to significant changes with respect to their financial reporting on the internet. Findings - Although we report a statistically significant increase in the number of firms providing financial disclosures on the internet from 2003 to 2007, we highlight a number of problem areas such as the extremely low level of voluntary disclosures (merely 7 per cent of the firms) and the apparent reluctance of listed firms to provide financial information unless it is mandatory to do so (such as financial summaries, financial ratios, share price performance and management reports). Originality/value - Our study provides detailed information on the state of internet financial reporting in Turkey before and after major regulatory changes and focuses not just on quoted firms but also on large unlisted industrials.
Keywords: Internet Financial Reporting (IFR); Turkey; Mandatory disclosures; Voluntary disclosures